A model of sustainable campus operations for Malaysian public universities - Razman, Ruzaimah (2017)
Currently, various initiatives have been undertaken by several universities around the world to ensure that their campus operates sustainably. Unfortunately, it seems that the efforts are still divergent and not systematically applied within the universities. Several models are available to be used as references for developing and implementing sustainability within campus. However, for local universities in particular, it is extremely important to understand the current situation whether there is a dearth of adequate conditions for the establishment and compliance of all phases of the models. As the issues of sustainability in Malaysia are still new, sustainability in universities should be performed in rather small steps according to the needs and situation of the university itself. Therefore, this study focuses on identifying the relevant Sustainable Campus Operation (SCO) initiatives to be implemented at the Malaysian public universities, and also determining the critical factors of governance that influence the successful implementation of the SCO initiatives. The investigation involves a quantitative approach using structured questionnaire survey, which was designed based on the items obtained from websites of sustainable universities around the world and also from literature review. The questionnaire survey forms were distributed to sixty-eight selected respondents at the Development Office or Sustainable Department of all local public universities. Based on the structural relationship model, it was found that the factor’s group of “Accountability to improve performance of SCO (AccF)” has the highest impact and more significant in implementing the thirteen relevant SCO initiatives as compared to the factor’s group of “Governance support to implement SCO (GovF)”. The established SCO model is the first that integrates all operations at the university, and highlights the importance for considering the governance support and accountability in analyzing and making decision of any potential initiatives towards campus sustainability. Hence, it can assist those involved in the planning of campus infrastructure and development to determine the most critical factors in implementing the SCO initiatives towards sustainability in Malaysian public universities.